Finite groups with S-permutable n-minimal subgroups. Issue 7 (3rd July 2018) - Pan, Hongfei; Qian, Guohua
ABSTRACT: We study the supersolvability of finite groups and the nilpotent length of finite solvable groups under the assumption that all their exactly n -minimal subgroups are S -permutable, where n is an arbitrary integer.